Multimodal Acupuncture Enhances Autonomic Balance and Reduces Blood Pressure in Adults - Kadek Buja Harditya; Anak Agung Istri Mas Padmiswari; Ida Ayu Suptika Strisanti; Komang Rosa Tri Anggaraeni (Jurnal Keterapian Fisik, 2026)
Background: Blood pressure regulation is influenced by autonomic nervous system balance, where increased sympathetic and reduced parasympathetic activity contribute to hypertension. Acupuncture may modulate autonomic function but combined somatic and auricular approaches remain underexplored. This study evaluated a multimodal acupuncture protocol combining Neiguan (PC6), auricular vagus, and Er Shen Men on autonomic function and blood pressure.   Methods: A randomized controlled trial with a pretest–posttest design was conducted in 60 adults aged 20–60 years, allocated into four groups: combination therapy, PC6 only, auricular vagus + Er Shen Men, and sham acupuncture. Interventions were applied twice weekly for four weeks. Outcomes included heart rate variability (SDNN, RMSSD, LF/HF ratio, and heart rate) and systolic and diastolic blood pressure. Data were analyzed using paired tests and ANOVA or Kruskal–Wallis tests with post hoc comparisons.   Results: The combination group showed significant improvements in SDNN, RMSSD, LF/HF ratio, and heart rate, along with reductions in systolic (−12.0 mmHg) and diastolic (−10.0 mmHg) blood pressure (p < 0.001). Single-intervention groups showed moderate changes, while the sham group showed minimal effects. Between-group differences were significant (p < 0.05), with greater improvements observed in the combination group.   Conclusion: Multimodal acupuncture is associated with improved autonomic function and reduced blood pressure, suggesting its potential as a non-pharmacological intervention for cardiovascular regulation.